[Not Quite] The Ketogenic Diet in a Pill - Andrew J Kim (Pediatric Neurology Briefs Publishers, 2015)
Researchers at Okayama University, Japan showed lactate dehydrogenase (LDH) inhibition suppresses neuronal excitation in vitro, reduces EEG discharges and seizures in rodent models, and may provide a novel mechanism for anticonvulsant medications in human patients.